Mode of drinking fluoridated milk: effect on intraoral fluoride concentrations. Issue 6 (15th December 2015) - Whitford, Gary M.; Riley, Danielle V.; Schafer, Tara E.; Looney, Stephen W.
Abstract : Objective: To determine the effect of the mode of drinking fluoridated milk on salivary and plaque fluoride concentrations. Methods: Fluoridated milk was ingested by 32 children in three ways: (a) directly from the container (1.0 and 5.0 mg F/litre), (b) through a straw with the tip between the lips (5.0 mg F/litre), and (c) with the tip deep in the oral cavity (5.0 mg F/litre). Saliva was collected at baseline and 2, 15, and 40 min and plaque at baseline and 20 min after drinking. Fluoride concentrations were determined using the electrode after HMDS‐facilitated diffusion. Results: The mode of drinking did not affect fluoride concentrations in saliva or plaque. The average 2‐min salivary concentrations were 65 ng F/mL for the 1.0 mg F/litre group and 276 ng F/mL for the three 5.0 mg F/litre groups ( P < 0.01). The average of the 15‐ and 40‐min salivary concentrations was 22 ng F/mL for the 1.0 mg F/litre group and 41 ng F/mL for the 5.0 mg F/litre groups ( P < 0.01). Plaque concentrations showed the same patterns as in saliva, that is, they were higher in the three 5.0 mg F/litre groups than in the 1.0 mg F/litre group and the differences among the 5.0 mg F/litre groups were not statistically significant. Conclusion: Salivary and plaque fluoride concentrations were independent of the mode of drinking but directly related to milk fluoride concentrations.